2005
DOI: 10.1007/s10750-005-4245-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Algal (Chlorella vulgaris) Food Level and Temperature on the Demography of Brachionus havanaensis (Rotifera): a Life Table Study

Abstract: We evaluated the combined effects of food (0.5 · 10 6 , 1.0 · 10 6 and 2.0 · 10 6 cells ml )1 of Chlorella vulgaris) and temperature (15, 20 and 25°C) on life history variables of B. havanaensis. Regardless of Chlorella density there was a steep fall in the survivorship of B. havanaensis at 25°C. Both food level and temperature affected the fecundity of B. havanaensis. At any given food level, rotifers cultured at 15°C showed extended but low offspring production. At 25°C, offspring production was elevated, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Offspring production may also be influenced by food level, e.g., higher density of Chlorella sp. increased offspring production of B. havanaensis (PAVÓN-MEZA et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Offspring production may also be influenced by food level, e.g., higher density of Chlorella sp. increased offspring production of B. havanaensis (PAVÓN-MEZA et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of predator (Asplanchna girodi) and low food levels can induce lorica and spine elongation in brachionid rotifers (B. quadridentatus: GILBERT, 2001; B. havanaensis: PAVÓN-MEZA et al, 2007). Temperature also has an effect on fecundity and life span of brachionid rotifers (see SNELL, 1986;GALKOVSKAYA, 1987;SARMA and RAO, 1991;PAVÓN-MEZA et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The responses of intrinsic rate of population growth to increasing temperatures were depended on rotifer species and algal food density. The intrinsic rates of population growth of B. havanaensis, B. rubens, B. urceolaris, B. forcatus and B. caudatus all significantly increased with temperature (Pavo´n-Meza et al, 2005;Hu et al, 2008;Tao et al, 2008). Similarly, the intrinsic rate of population growth of the sibling species LE9 in B. calyciflorus complex from Wuhu, China was the highest at 28 xC, at 13 and 18 xC it was the lowest.…”
Section: Discussionmentioning
confidence: 99%
“…These results are largely based on zooplankton species cultured at constant temperatures. For example, it has been shown that an increase in temperature from 15 to 25°C, doubled the net reproductive rates of the rotifer B. havanaensis , but decreased the lifespan by about 60% . However, in certain waterbodies, water temperature may vary widely over a diel period: e.g., 5–25°C.…”
Section: Discussionmentioning
confidence: 99%